(untitled) (Journal of actual problems of jurisprudence, 2018)
At present in the Constitutions and normative legal acts of many countries recognize the existence of national, ethnic and linguistic minorities. Along with these actions are carried out in the area of protection and non-discrimination of national, ethnic and linguistic minorities, the preservation of their individual differences and identities. To ensure the institutional living conditions of national, ethnic and linguistic minorities in any country, it is necessary to adopt of certain constitutional rules and legal acts aimed at the regulation and protecting the rights of national minorities. In this article, the authors discusses the legislative acts of the Republic of Poland, regulating the relations connected with the preservation and development of cultural identity of national and ethnic minorities, the preservation and development of regional language, as well as defining the tasks and competency of public administration bodies and units of local self-government in the area of these questions. Key words: national minorities, ethnic minorities, minority language, the legal status of minorities.